2018
DOI: 10.24235/eduma.v7i2.3357
|View full text |Cite
|
Sign up to set email alerts
|

Menakar Kemampuan Berpikir Tingkat Tinggi Calon Guru Matematika Melalui Level Hots Marzano

Abstract: Makalah ini bertujuan untuk menakar kemampuan berpikir tingkat tinggi calon guru Matematika. Penulis menggunakan level HOTS Marzano yang terbagi dalam lima dimensi kemampuan berpikir; (1)pengambilan keputusan, (2)Pemecahan masalah, (3)Analisis kesalahan, (4)abstraksi, dan (5) analisis dan klasifikasi perspektif. Instrument yang digunakan diadaptasi dari Marzano Rubrics for Spesific task or Situations (1993). Penelitian ini merupakan penelitian kuantitatif dengan melibatkan 34 mahasiswa program studi Tadris Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
4
0
4
Order By: Relevance
“…These learning activities are able to train students' higher-order thinking skills. This is similar to the results of the study of Gradini et al (2018), which argues that to be able to train higher-order thinking skills, students need to be accustomed to learning activities, honing students' thinking skills is considered an important educational goal and teachers have an important role in stimulating students' higher-order thinking. Cognitive processes involved with higher-order thinking strategies are directly related to the use of knowledge for problem-solving.…”
Section: Resultssupporting
confidence: 85%
“…These learning activities are able to train students' higher-order thinking skills. This is similar to the results of the study of Gradini et al (2018), which argues that to be able to train higher-order thinking skills, students need to be accustomed to learning activities, honing students' thinking skills is considered an important educational goal and teachers have an important role in stimulating students' higher-order thinking. Cognitive processes involved with higher-order thinking strategies are directly related to the use of knowledge for problem-solving.…”
Section: Resultssupporting
confidence: 85%
“…A study investigating students' Higher-Order Thinking Skills (HOTs) in mathematics within Aceh Tengah District revealed concerning outcomes. The research identified inadequate student mastery in tackling HOTs-based questions (Gradini, Firmansyah, & Noviani, 2018), indicating low skill levels. Moreover, the study highlighted the significant challenge mathematics teachers face in effectively stimulating students' development of HOTs.…”
Section: Introductionmentioning
confidence: 95%
“…Dengan demikian jenjang kognitif siswa yang diukur masih dalam tingkat aspek mengingat (C1), memahami (C2), menerapkan (C3), menganalisis (C4) dan mengevaluasi (C5) [16]. Soal yang diberikan pada siswa untuk soal penilaian harian seharusnya soal bertipe HOTS karena ditinjau dari segi tujuan pelaksanaan penilaian harian sebagai tolak ukur standar nasional dalam mencapai kualitas siswa, maka sudah seharusnya terdapat komponen soal dengan kemampuan berpikir tingkat tinggi [17].…”
Section: Gambar 2 Diagram Kualitas Soal Hots Dan Lotsunclassified
“…Dibuktikan dengan 20 soal HOTS yang di analisis terdapat perbandingan kualitas soal HOTS dengan persentase sebesar 60% yang termasuk kategori sebagian besar yang memenuhi karakteristik soal HOTS dan kualitas soal LOTS dengan persentase sebesar 40% yang termasuk kategori kurang dari setengah yang memenuhi karakteristik soal HOTS. Butir soal yang memenuhi karakteristik HOTS sejumlah 15 soal yang terdiri dari nomer 1,2,3,4,5,6,9,10,11,12,13,15,17,19,20. Sedangkan butir soal yang memenuhi karakteristik LOTS sejumlah 5 soal yang terdiri dari nomer 7,8,14,16,18.…”
Section: Kesimpulan Dan Saranunclassified